Is epistemological reliabilism consistent with grammatical evidentiality and conjunct/ disjunct marking? - Łukasiewicz, Elżbieta (Scripta Neophilologica Posnaniensia, 2020)
The paper discusses how evidentiality and conjunct/disjunct marking in grammar are related to reliabilism, a contemporary theory of epistemic justification developed within the Anglo-American analytic tradition. It is assumed that many problems and ideas concerned with theories of knowledge, and with justification of beliefs in particular, which are widely discussed in contemporary philosophical debates, are worth reconsidering in the light of what grammars of natural languages impose on the epistemic agent. Section two explains how the notions of knowledge, belief and justification are understood in the paper. The section also outlines the major problems concerning the internalist justification of beliefs. Section three presents an externalist view on the problem of justification: process reliabilism. The reliabilist theory of justification is set in the context of two grammatical categories: evidentiality and conjunct/disjunct marking (egophoricity). Since the two categories are still little known, section four offers a brief presentation of evidentiality and egophoricity in grammar, illustrated with data from two languages. Finally, section five addresses the problem whether the premises of reliabilism are reconcilable with ‘natural epistemology’ encoded in grammar. The final conclusion says that the externalist premises of reliabilism are certainly not congruent with grammatical evidentiality and evidentialityrelated categories, but they are not logically inconsistent therewith. Furthermore, since the reliabilist program declares interest in ‘folk epistemic practices’, the approach might greatly benefit from what ‘natural epistemology’ tells us about epistemic folk concepts and epistemic practices employed by speakers of diverse world languages.